Desain Soal Model PISA Konteks Covid-19: Review Pakar - Jevikha Mahardita; Hartatiana Hartatiana; Ambarsari Kusuma Wardani; Sujinal Arifin (JEMST (Jurnal of Education in Mathematics, Science, and Technology), 2021)
This study aims to produce valid PISA model math problems in the Covid-19 context by connecting mathematical concepts with events in the real world. This study uses the development of the PISA model problem by Tessmer, namely formative evaluation, against the reviews of several mathematicians in assessing the design of the questions that have been designed. The data collection technique used is walk through, namely expert reviews of content, constructs, and language to determine the validity of PISA questions in the context of Covid-19. This article focuses more on the discussion of the results of expert reviews activities. So it can be concluded from the results of this study that 6 PISA model questions with the Covid-19 context in the form of descriptions have met the valid criteria based on the validation results from experts and reviews provided by colleagues.